2014
DOI: 10.1890/13-2244.1
|View full text |Cite
|
Sign up to set email alerts
|

Habitat‐ and rainfall‐dependent biodiversity responses to cattle removal in an arid woodland–grassland environment

Abstract: Biodiversity conservation in rangeland environments is often addressed by removing livestock, but inconsistent responses by biota mean that the efficacy of this form of management is hotly debated. Reasons for this inconsistency include the usually short duration and small spatial scale of manipulations compared to the area of grazing properties, as well as divergent responses amongst biota. In low‐productivity arid environments, the pulse‐reserve dynamic also complicates the outcome of manipulations. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 93 publications
1
27
0
Order By: Relevance
“…Riparian areas and shrublands ranked high in vegetation diversity, while rocky habitats ranked high in temporary and permanent cover (dens). This is consistent with observations that arid environments have patches of more productive areas embedded in a matrix of lower productivity (Frank et al 2014b). In my study area, shrublands, riparian, and rocky patches were embedded within spinifex grasslands.…”
Section: Does the Topographic Complexity Of Rocky Outcrops Create Higsupporting
confidence: 92%
“…Riparian areas and shrublands ranked high in vegetation diversity, while rocky habitats ranked high in temporary and permanent cover (dens). This is consistent with observations that arid environments have patches of more productive areas embedded in a matrix of lower productivity (Frank et al 2014b). In my study area, shrublands, riparian, and rocky patches were embedded within spinifex grasslands.…”
Section: Does the Topographic Complexity Of Rocky Outcrops Create Higsupporting
confidence: 92%
“…Livestock removal is often considered an essential tool for vegetation restoration and conservation in arid and semiarid rangelands (Frank et al. ). However, little is known about how livestock removal affects woody encroachment because isolating the effects of browsing on rangeland woody plant dynamics requires long‐term, controlled livestock exclusion experiments, which are rare in Eurasian rangelands (Wesche and Treiber ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Maher et al (2010) found that an absence of kangaroos in fenced plots in kwongan of southwestern Australia would result in the much more extensive and rapid encroachment of Allocasuarina huegeliana than it would in unfenced plots. Livestock removal is often considered an essential tool for vegetation restoration and conservation in arid and semiarid rangelands (Frank et al 2014). However, little is known about how livestock removal affects woody encroachment because isolating the effects of browsing on rangeland woody plant dynamics requires long-term, controlled livestock exclusion experiments, which are rare in Eurasian rangelands (Wesche and Treiber 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Other study showed that increasing grazing pressure changes chemical and physical properties of topsoil, enhancing soil degradation processes, and eventually affecting the structure of vegetation (Kölbl et al, ). Grazing can stimulate growth of some grazing‐tolerant plant species and contribute to changes in species diversity, and productivity (Augustine & McNaughton, ; Frank, Wardle, Dickman, & Greenville, ). This result supported the concept that grazing had a significant effect on the contribution of some functional groups shaping the structure of vegetation (Bermejo et al, ).…”
Section: Discussionmentioning
confidence: 99%